The professional practice of teaching - Fraser, Deborah, 1961-; McGee, Clive (South Melbourne, Vic. : Cengage Learning, 2008)
'This text provides a unique and contemporary overview of teaching and learning in Aotearoa, New Zealand and will be relevant to teachers across the primary, secondary and tertiary levels. This updated third edition comprises fifteen chapters that address a broad range of themes and issues, including the practical challenges of teaching and learning, understanding curriculum and appreciating the broader social, historical and political contexts of education. It provides comprehensive national and international pedagogical knowledge that is important for both pre-service and in-service teacher education.'--Provided by publisher
Includes index
Keywords: Teaching; Learning, Psychology of; Curriculum planning; Classroom management